Informal supply chains of wild meat from rural Amazonia and food security in an urban center - Fiorella Briceño Huerta; Michael P. Gilmore; Mark Bowler; Brian M. Griffiths (Conservation Biology, 2026)
Iquitos, the most populated city in the Peruvian Amazon, is a hub in the regional supply chain of wild meat and supplies urban consumers. Studies on wild meat consumption have focused primarily on markets, limiting the scope of species considered to those that are economically valuable and potential inferences from those data. We conducted interviews with 1548 households in Iquitos across all four districts to assess wild meat consumption rates for 7831 people in those households. We used species‐ and source‐specific conversion factors to estimate biomass consumed from different species and sources in the supply chain. We estimated that 1786 t (95% CI 636.48–3317.62) of wild mammal meat were consumed in 2019 in Iquitos, which is about 4.25 kg (95% CI 1.54–8.02) per person per year. Markets supplied 57.22% of all wild mammal meat, but 14.67% was purchased from other sources and 27.85% was not purchased. Paca ( Cuniculus paca ) and collared peccary ( Dicotyles tajacu ) were the most heavily consumed species, mostly from markets. The majority of meat from other species, such as the woolly monkey ( Lagothrix lagotricha ) and capybara ( Hydrochoerus hydrochaeris ), was traded outside markets. Our results indicated that wild mammal consumption rates may be much higher in Iquitos than previously reported, likely because social connections accounted for about half of the supply chain; consumers are receiving wild meat as gifts or were hunting themselves. The breadth of mammal meat consumption demonstrates the contributions of hunting to the food security and economic stability of consumers in Iquitos and the potential for sustainable supply chains of some mammals.

Source-sink dynamics facilitate mammal recovery after unsustainable hunting in a community-managed natural protected area in the Peruvian Amazon - Brian M. Griffiths; Ellen Nirenblatt; Chelsie Romulo; Mark Bowler; Fiorella Briceño Huerta; Michael P. Gilmore (Ambio, 2026)

Vocal Repertoire of the Ucayali Bald Uakari (Cacajao ucayalii) - Julián León; Mark Bowler (International Journal of Primatology, 2026)
All primate species produce vocalizations for complex communication, conveying a wide range of information, regulating social interactions, coordinating activities, and serving as antipredator strategies. Together, these vocalizations form a species' vocal repertoire. However, despite their widespread presence and ecological significance, the vocal repertoires of less than 15% of primate taxa have been documented to date. The purpose of this study was to quantitatively characterize the vocal repertoire and behavior of a wild population of Ucayali bald or red uakaris ( Cacajao ucayalii ), a rare Amazonian platyrrhine primate. We analyzed and categorized 1,155 red uakari vocalizations using a combination of machine-learning-based random forest analyses, bioacoustic analysis, and field observations. We identified and described 12 acoustically distinct call types, two of which were not previously reported ( High-chick and Shriek ). The Hic was the most common vocalization, both in context and frequency of use. Some calls were specific to age, sex, or context, while others occurred across a range of situations. The vocal repertoire exhibited properties of both graded and discrete calls, depending on the call type and its apparent function. The uakaris’ tail plays a key role in the species’ acoustic-visual multimodal communication, as evidenced by the frequent combination of different call types and tail wagging, probably to draw attention from other group members and emphasize the transmission of information. The bioacoustic characterization of the Ucayali bald uakari's vocal repertoire provides a groundwork for potential acoustic monitoring of this species and the potential use of uakari monkeys as models for studying multimodal communication in primates.

Socioeconomic drivers of wild meat consumption in the city of Iquitos, Peru - Fiorella Briceño Huerta; Michael P. Gilmore; Mark Bowler; Brian M. Griffiths (Conservation Biology, 2025)
Wild meat represents a vital source of micro‐ and macronutrients for forest‐dwelling people; however, city dwellers with access to animal protein from different animals may also consume large amounts of wild meat as part of their customs and traditions, to diversify their diets, to maintain connections to their rural kin, and to access meat without having to pay the high prices of domestic meat in the city. The aggregate urban and rural demand for wild meat consumption demonstrates a great risk for overhunting highly preferred and vulnerable species and degrading already fragile Amazonian ecosystems and the food security of people in rural areas. We assessed the effects of socioeconomics factors on wild meat consumption in the city of Iquitos in the Peruvian Amazon. We conducted 1548 interviews with consumers across the city of Iquitos and collected socioeconomic and wild meat consumption data. We used a double hurdle model to estimate simultaneously the probability of a consumer eating wild meat each week and their consumption rate based on 10 variables. In final parsimonious models, monthly income, location in the city (district and distance to market), amount of education, and amount of time spent in Iquitos were all important factors determining consumption rate. We predicted that consumption rates would vary across the city and in some areas would be as high as >7 kg·person −1 ·year −1 . The spatial distribution of wild meat consumption showed that people in newer, rapidly growing parts of the city consumed more wild meat and were therefore more dependent on sustainable supply chains. We recommend that consumers who have very high predicted consumption rates may be useful targets for conservation efforts to reduce that consumption, such as culturally relevant, informal educational programs. In our study, these people migrated from rural areas and live along the Iquitos–Nauta Road and are wealthy consumers in downtown Iquitos.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Observational Needs Supporting Marine Ecosystems Modeling and Forecasting: From the Global Ocean to Regional and Coastal Systems - Antonietta Capotondi; Michael Jacox; Chris Bowler; Maria Kavanaugh; Patrick Lehodey; Daniel Barrie; Stephanie Brodie; Samuel Chaffron; Wei Cheng; Daniela F. Dias; Damien Eveillard; Lionel Guidi; et al. (Frontiers in Marine Science, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Potentially infanticidal behavior in the Amazon river dolphin (Inia geoffrensis) - Mark T. Bowler; Brian M. Griffiths; Michael P. Gilmore; Andrew Wingfield; Maribel Recharte (acta ethologica, 2018)

Assessment of mammal reproduction for hunting sustainability through community‐based sampling of species in the wild - Pedro Mayor; Hani El Bizri; Richard E. Bodmer; Mark Bowler (Conservation Biology, 2017)
Wildlife subsistence hunting is a major source of protein for tropical rural populations and a prominent conservation issue. The intrinsic rate of natural increase. ( r max ) of populations is a key reproductive parameter in the most used assessments of hunting sustainability. However, researchers face severe difficulties in obtaining reproductive data in the wild, so these assessments often rely on classic reproductive rates calculated mostly from studies of captive animals conducted 30 years ago. The result is a flaw in almost 50% of studies, which hampers management decision making. We conducted a 15‐year study in the Amazon in which we used reproductive data from the genitalia of 950 hunted female mammals. Genitalia were collected by local hunters. We examined tissue from these samples to estimate birthrates for wild populations of the 10 most hunted mammals. We compared our estimates with classic measures and considered the utility of the use of r max in sustainability assessments. For woolly monkey ( Lagothrix poeppigii ) and tapir ( Tapirus terrestris ), wild birthrates were similar to those from captive populations, whereas birthrates for other ungulates and lowland‐paca ( Cuniculus paca ) were significantly lower than previous estimates. Conversely, for capuchin monkeys ( Sapajus macrocephalus ), agoutis ( Dasyprocta sp .), and coatis ( Nasua nasua ), our calculated reproductive rates greatly exceeded often‐used values. Researchers could keep applying classic measures compatible with our estimates, but for other species previous estimates of r max may not be appropriate. We suggest that data from local studies be used to set hunting quotas. Our maximum rates of population growth in the wild correlated with body weight, which suggests that our method is consistent and reliable. Integration of this method into community‐based wildlife management and the training of local hunters to record pregnancies in hunted animals could efficiently generate useful information of life histories of wild species and thus improve management of natural resources.

Climatic amplification of the numerical response of a predator population to its prey - Berlinda Bowler; Charles Krebs; Mark O'Donoghue; Jim Hone (Ecology, 2014)
We evaluated evidence of an effect of climate on the numerical response of a coyote ( Canis latrans ) population to their keystone prey, snowshoe hares ( Lepus americanus ), in a Canadian boreal forest. Six a priori hypotheses of the coyote numerical response were developed that postulated linear, nonlinear, additive, and interactive effects of prey and climate. Model selection procedures showed the North Atlantic Oscillation (NAO) had the strongest effect on the coyote numerical response via its interaction with snowshoe hare density, while other large‐scale climate indices had very weak effects. For a given snowshoe hare density, a negative value of the NAO amplified the abundance of coyote and a positive NAO decreased coyote abundance. We hypothesize that the coyote numerical response is ultimately determined by the coyote functional response influenced by winter conditions determined by the NAO.

Multilevel Societies in New World Primates? Flexibility May Characterize the Organization of Peruvian Red Uakaris (Cacajao calvus ucayalii) - Mark Bowler; Christoph Knogge; Eckhard W. Heymann; Dietmar Zinner (International Journal of Primatology, 2012)

Diet and Food Choice in Peruvian Red Uakaris (Cacajao calvus ucayalii): Selective or Opportunistic Seed Predation? - Mark Bowler; Richard E. Bodmer (International Journal of Primatology, 2011)